Improving the arrow selection process in archery: the stiffness variation pattern matters - Kuch, A.; Laguillaumie, P.; Durand, F.; Debril, J.-F.; Monnet, T. (Sports Engineering, 2025)
In a precision sport such as archery, optimizing the arrows used and how they are assembled is essential to perform at an elite level. Since there are many mechanical characteristics to consider, such as their mass, stiffness, diameter, straightness, and fletching position, this study aimed to assess which parameters should be prioritized for the arrow selection process. The mechanical properties of sixty arrow shafts were obtained using an automated testing bench, and a sinusoidal wave was used to model the stiffness variation around the shaft cross-section. A controlled assembling procedure allowed the characterization of the positions of the vanes relative to the stiffness extrema. The arrows were then shot at 70 m indoors, using a shooting machine, thus removing the human and wind-induced variability. Two significant multiple stepwise regression models partially predicted the vertical or horizontal position of the arrows on target, using the mass and the mean stiffness, or the mean stiffness and stiffness variation amplitude, respectively. Furthermore, a combination of the mass, mean stiffness and stiffness frequency was found to better explain the relative proximity of arrow marks with each other, suggesting that the ability to control the stiffness variation pattern is required.